(:unas) unassigned - Yoshimichi YAMAMOTO; Wibool WUTTHIYAN; Kunihiko IIDA; Kyohei KAWAI (My University, 2007)
We tried to devise a method for estimating the degree and geographic extent of tsunami damage using satellite photographs in two case studies of damage to Thailand's west coast due to the Indian Ocean tsunami. Following results were obtained from those case studies: the extent of a flood area can be generally estimated from discoloration of vegetation zone assuming such vegetation originally existed along the coast; house damage could be estimate by deciphering whether each roof was lost or not, however if the roof remained, the degree of damage to walls and pillars could not be discerned.Therefore, we develop a method to get marginal thickness of walls and marginal width of pillars which break on arbitrary positions using a distribution of tsunami heights on a coastline and a distribution of ground heights. In addition, the extent of a flood area can be presumed if there are the above-mentioned distribution data and elapsed data of sea water levels at the time of a tsunami invasion.
Keywords: Earthquake and Tsunami Effects